Climate-Resilient Governance: Nurturing Eco-Friendly Public Services at the Grassroots in Kerala, India - Chathukulam, Jos (Unisia, 2024)
Efforts to integrate climate resilience into public services are evident in Kerala’s developmental landscape. While climate and disaster risk-informed project planning and implementation are integral components of public service delivery in the region, climate and environmental concerns are often overlooked in the realm of politics in Kerala. Local governments in Kerala play a central role in ensuring the scalability and sustainability of climate-resilient initiatives. By integrating climate considerations into decision-making processes, Kerala’s public sector workforce fosters eco-friendly attitudes by incorporating digital public goods and e-governance in mainstreaming local service delivery, thereby contributing to broader climate action efforts. This paper critically examines the local climate-resilient activities as forms of ’public services’, emphasizing digital public goods. While the rhetoric is that there is a Kerala model of participatory local climate governance that prioritizes environmental concerns, the reality is far from different.